Assessment of Clientele Satisfaction of Selected KVKs in Mizoram - Lalhmachhuana, P.; Devarani, Loukham (Indian Journal of Hill Farming, 2017)
Clientele satisfaction is a major indicator for the effectiveness of any service rendered and performance of an organization. The study was conducted to assess the clientele satisfaction level of services provided by three selected KVKs of Mizoram viz, Kolasib, Lunglei and Aizwal. A total of 80 farmer clientele and 10 extension functionaries were the respondents of the study. Majority of the clientele (60.00%) had expressed medium level of satisfaction. Satisfaction level was found highest in customer service (71.51%) followed by quality (68.24%), relevancy (59.44%) and usefulness (56.03%). Education level of the respondents was found to have negative and significant association with their level of satisfaction. The clientele found the farm visits convenient, subject matters well organized and services compatible with their farming system. The major contributors for low satisfaction were lack of information on market and less & inefficient vocational training and these are the areas where intervention is required to improve the satisfaction level of the clientele.